2012
DOI: 10.1111/j.1349-7006.2012.02374.x
|View full text |Cite
|
Sign up to set email alerts
|

Prosaposin, a regulator of estrogen receptor alpha, promotes breast cancer growth

Abstract: Prosaposin, a secreted protein, is a well-known pleiotropic growth factor. Although a previous report has indicated that prosaposin is overexpressed in breast cancer cell lines, the role of prosaposin in the development of breast cancer remains to be identified. Here, we first revealed that prosaposin upregulated estrogen receptor alpha expression, nuclear translocation and transcriptional activity by western blot, immunofluorescence assay and dual luciferase reporter gene assay, respectively. Furthermore, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 36 publications
(46 reference statements)
1
39
0
Order By: Relevance
“…6B). To further understand the mechanism of action for PSAP, we analyzed phosphorylation of ERK and Akt in 4T1 cells, because PSAP induces phosphorylation of ERK and growth of breast cancer cells(13) and saposin C, including the functional domain of PSAP, promotes survival of prostate cancer cells via Akt phosphorylation(14). PSAP treatment induced phosphorylation of Akt at T308 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6B). To further understand the mechanism of action for PSAP, we analyzed phosphorylation of ERK and Akt in 4T1 cells, because PSAP induces phosphorylation of ERK and growth of breast cancer cells(13) and saposin C, including the functional domain of PSAP, promotes survival of prostate cancer cells via Akt phosphorylation(14). PSAP treatment induced phosphorylation of Akt at T308 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6I). Previous studies showed that PSAP induces mammary cancer growth(13) and inhibits metastasis(15). Our results are consistent with these reports.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, we focused our attention on the intersections between SKOV-3 and FT194 cells and we observed that they include several interesting genes such as: PSAP, FGF18, CDH6, ROR1, RBPJ and DNMT3B whose role in cell proliferation, cell survival and tumorigenic process has already been reported. In particular, PSAP (prosaposin) is a pleiotropic growth factor able to prevent cell death or apoptosis and to promote cell survival [68]; FGF18 controls migration, invasion and tumorigenicity of ovarian cancer cells [69]; CDH6 is a new TGF-beta target modulated as a mesenchymal marker in EMT [52]; ROR1, a receptor tyrosine kinase orphan receptor 1, is involved in migration, invasion and EMT in ovarian cancer cells [70]; RBPJ (recombination signal-binding protein Jk) is a key transcription factor in the Notch signaling pathway and its inhibition reduces cell growth [71]; DNMT3B encodes a DNA methyltransferase involved in de novo DNA methylation whose role in cancer development is not clear but several reports suggest a role as tumor suppressor [72]. …”
Section: Resultsmentioning
confidence: 99%
“…Other studies, have evaluated the potential of Prosaposin as an important molecule in the protection of cancer cells, such as prostate (Koochekpour et. al, 2012) and breast cancer cells (Wu et al, 2012), enabling them to survive and proliferate, also suggesting the presents of Prosaposin as a potential drug target in the development of treatments for personal cancer therapies. Patton et al (1997) demonstrated the presence of Prosaposins in human, cow and goat's milks.…”
Section: Introductionmentioning
confidence: 99%